Czas melancholii - czasem przemian (transgresji) czy czasem destrukcji? - Tański, Marek (Przestrzenie Teorii, 2007)
The main objective of the article is to discuss the time of melancholy. The author tries to triangulate the definition of the time of melancholy with the classic Freud model, concentrating on the role of the back reflects in every activities, lower of feeling and the needs for a system of morał values, untill to the self-assucusation and especially the expectation onto punishment. The starting point of this article has been organized in the model of the constantly repetition of the doubt, including the sceptical oneself-reflection, which does not onto no transgression (the characteristic point of the first stage). The time of melancholy (in the second stage) begins in to remind of the time of transgression, including the evaluating of internal area. To see the issue in a broad perspective, the author takes into account the relation between a man and his undertakings, such as: eftorts to be a through man, free from the despair, abandonments of lost object and in necessity to retrieval of oneself.